An accessory role for the diacylglycerol moiety of variable surface glycoprotein of African trypanosomes in the simulation of bovine monocytes - Sileghem, M.R.; Saya, R.; Grab, D.J.; Naessens, Jan (Elsevier, 2001)
The membrane-associated form of the variable surface glycoprotein (mfVSG) from African trypanosomes is a potent macrophage activator capable of inducing production of tumor necrosis factor z (TNFalfa) in both bovine and murine models. Using a bovine model. we have re-investigated the hypothesis that the diacylglycerol moiety of the glycosylphosphatodylinositol (GPI) anchor is involved in macrophage activation and might be the actual parasite toxin- The anchor of the variable surface glycoprotein (VSG) was labeled with ;H-myristic acid and VSG purified in its membraneassociated form. The dimyristylglycerot moiety of the anchor was. released by phospholipase C cleavage. Integrity of the anchor and efficiency of cleavage was verified by autoradiography and methanol:hexane extraction. For analysis of biological function, bovine monocytes were used which had been incubated with bovine interferon y (primed) or with culture medium (unprimed). The VSG purified in its membrane-associated form was found to stimulate both primed and unprimed cells to secrete TNFalfa The same preparation from which the dimyristylglycerol moiety had been cleaved was no longer able to stimulate unptimed cells but could still stimulate primed cells. Our data indicate that the presence of the dimyristylglycerol is not an absolute requirement for induction of TNFalfa production but can substitute for the interferon y priming. Therefore, we favor the hypothesis that stimulation of macrophages to secrete TNFalfa by the mtVSG is mediated by an as yet unknown trigger moiety and is facilitated by the dimyfstylglycerol anchor.